The Urgency of Agile Leadership Training to Produce Competitive Startups in the Vuca Era - Singgih, Rahadi Pratomo; Sari, Mira Permata (LPPM Institut Pendidikan Nusantara Global, 2024)
In Indonesia, many types of start-up businesses or start-up companies have started to emerge and are growing very rapidly. We can easily find start-up companies in various sectors. Of these startups, some are expected to emerge from campuses through student startups that have big ideas and ideas and are supported by business incubators at each university. However, unfortunately, not all student startups can run smoothly. Many of them failed and were eventually forced to close. One of the reasons is the lack of guidance and training from the university where he attends. The important provision that must be given now is how to become an agile leader or entrepreneur in the current VUCA era. This research is aimed at answering the question of how training or guidance is provided by universities to startup management students, and how 'Agile Leadership' training is implemented. This is qualitative research with a case study approach at the XYZ campus in Jakarta. Data collection was carried out using semi-structured interviews with 15 startup management students. The results of this research show that